Konsep Manusia Pemberontak Menurut Albert Camus - Yohanes Jettly Meicen Polii (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2023)
This article explores the Concept of The Rebel as expressed by the philosopher and renowned writer, Albert Camus. Through a critical analysis of Camus' works, this thesis aims to understand the essence and implications of the rebel man in the context of modern life. The research methodology employed includes textual analysis and philosophical examination of Camus' writings related to this concept. The findings of this thesis indicate that, according to Camus, the rebel man is an individual who actively opposes injustice, absurdity, and oppressive authority in life. Rebellion is not an act of violence or destruction, but a moral and existential stance that strives for freedom and human dignity. In Camus' works, the rebel is regarded as a symbol of authentic existence, rejecting blind conformity to social norms that stifle individual freedom. Through the development of this concept, the thesis also provides a deeper understanding of the importance of rebellion in social and political contexts. Camus' concept of the rebel man leads us to raise critical questions about justice, freedom, solidarity, and human responsibility as individuals in this complex society. In modern life, this understanding presents relevant and profound philosophical challenges and reflections.